Hellenistic Amphora Stamps From Elaiussa - Kızılarslanoğlu, H. Asena; Alkaç, Erkan (OpenEdition, 2018)
Elaiussa is situated on the coastal strip of the Olba region, which extends between the Kalykadnos and Lamos Rivers (Map 1). The city was part of the Eastern Mediterranean trading community from the 2nd century B.C. to the 7thcentury A.D., due to its location on the coastal road, as well as to its access to rich natural and agricultural sources. The finds from the excavations since 1995 furnish insight into the built environment and city life in Elaiussa, especially during the Roman and Late ...
Keywords: 13. Climate action; 11. Sustainability; 8. Economic growth; 14. Life underwater; 15. Life on land; 3. Good health; 12. Responsible consumption